Towards Clasification Exploration in Spatial Crowdsourcing Domain: A Systematic Literature Review - et.al, Shirley Salimun (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Today, spatial crowdsourcing concept has been widely applied in various fields. The increasing ofmobile user and adoption of social network has catalyst spatial crowdsourcing growth. It has madevarious types of data to be easily collected and transmitted from different geographical location.However, the massive amounts of task in spatial area bring challenges for the online system tomanage especially when the task is heterogeneous, and the interactions are dynamic. Such scenario has alerted the researchers to understand different types of information in order to make taskassignment reliable and efficient.This study investigates current state of task assignment for spatialcrowdsourcing. It basically, aims to identify several issues like trend in publication and crowdcomputing areas that studies task assignment in crowdsourcing. We used Systematic LiteratureReview (SLR) method for analysing the trends and significance of task classification for betterdynamic crowd-computing.